2016
DOI: 10.4236/opj.2016.67017
|View full text |Cite
|
Sign up to set email alerts
|

Light Reflection by Cuticles of Chrysina Jewel Scarabs: Optical Measurements, Morphology Characterization, and Theoretical Modeling

Abstract: Cuticles of some Chrysina scarabs are characterized by flat, graded, and twisted structures of nanosized chitin fibrils. As inferred from SEM images, each species has its own spatial period or pitch P which is dependent on the depth z through the cuticle. From Berreman's formalism, taking into account the corresponding P(z) dependence, we evaluate reflection spectra of C. aurigans and C. chrysargyrea scarabs. The spectra display the main spectral features observed in the measured ones when small sections of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Other authors reported a graded pitch ranging between 240 and 360 nm from the analysis of SEM images taken on the cuticle of silver-like C . chrysargyrea 18 . This variation of pitch is not consistent with the reflection of left-handed polarized light in the near infrared.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other authors reported a graded pitch ranging between 240 and 360 nm from the analysis of SEM images taken on the cuticle of silver-like C . chrysargyrea 18 . This variation of pitch is not consistent with the reflection of left-handed polarized light in the near infrared.…”
Section: Resultsmentioning
confidence: 99%
“…Both silvery and golden beetles can be found in different specimens of the same species as in C . chrysargyrea 18 . Figure 1(b) shows a photo of a silvery C .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been a growing interest on the polarization properties of these helicoidal structures [5,6]. This has lead to the creation of models of the structure that reproduce its optical response [7] and to biomimetic fabrication of similar structures [8].…”
Section: Populärvetenskaplig Sammanfattningmentioning
confidence: 99%